Planda Düzensiz Betonarme Bir Yapının Düşey Ve Yatay Yükler Altında Davranışının İncelenmesi - Nam, Cihan (Fen Bilimleri Enstitüsü, 2015)
Tezde ilk olarak yapının taşıyıcı elemanlarındaki kesit tesirleri hesabına esas olan yöntemler ele alınarak en elverişsiz koşulların hangi şartlarda oluştukları belirlendi. Bu şekilde kullanılan yöntemlerin sonuçları karşılaştırılarak betonarme hesaba esas zorlanmalar tespit edildi. Daha sonra betonarme hesaba geçilerek elemanların donatıları belirlendi ve ilgili kalıp planları çizildi. Yatay yükler altında hesap eşdeğer statik yöntem ile ve ayrıca dinamik analiz için mod birleştirme yöntemi ile ayrı ayrı yapıldı. Daha önce sadece düşey yüklere göre hesaplanmış olan döşeme ve kiriş elemanların ise yatay yüklerin etkisinden dolayı gerekli olan ilave donatılar tespit edilerek eklendi. Temel için ayrı bir model oluşturularak sonlu plak elemanlara yatak katsayısı ile binadan gelen ağırlıklar ve yatay etkiler yüklenerek betonarme hesaba esas iç kuvvetler bulundu.

A business center whose carrier system is made up with frames and shear walls is taken as an example for this thesis. In the supposition of first chapter, material properties, loading conditions, initial section dimensions, physical and geometrical properties of the structure, responds types, soil conditions are determined in order to force the structure. First of all, on which load type the very convienence conditon at the sections will be occure is determined which will be the basis of section responds on the structure frame elements. By comparing the methods used forces are determined on the frame sections. Then reinforced concrete calculation is performed and corresponding drawings are made up. Equivalent Seismic Load Method and dynamic analysis with Mode-Superposition method are performed separately in order to determine the horizontal respond of the structure. Due to the shape of structure, in equivalent earthquake static analysis, it is observed that there is a tendency towards torsion beside horizontal drift under horizontal loads. Therefore, due to the torsional irregularity, the calculation is repeated with new eccentricity. Because the main axis of carriying system are not parallel, both earthquqke directions are combined in order to determine the very convenience condition for the reinforcement calculations. Taking everything into account, both the design and the requirements of a carrying ststem that has a sufficient resistance against erthquake is experienced in this thesis. It is also possible that design of other structure systems can be performed like this.
Assesment Of An Irregular Reinforced Concrete Building Under Vertical And Horizontal Loads
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2001
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2001
Keywords: Üçgen bina; Kirişsiz döşeme; Perdeli sistem; Trianglar building; Shear walls